Terapi dengan Dinydroartemisinin Piperaquine (DHP) dapat Mencegah Terjadinya Anemia Tetapi Tidak Dapat Mencegah IUGR pada Mencit Bunting yang di Infeksi Plasmodium berghei - Andriana, Diah (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2018)
ABSTRACTInfection of malaria with Plasmodium falciparum during pregnancy is associated with infection in the placenta and extensive adverse effects on the mother and the fetus it contains include one of them anemia in pregnant women while in the fetus IUGR occurs. Eighteen pregnant mice which were infected with Plasmodium berghei were divided into 2 groups, namely the control group and the treatment group treated with DHP. Mice are surgically removed after the 18th day after infection. Anemia was examined by looking at Hb and IUGR checked by testing the fetus. The results were found that DHP therapy in pregnant mice in Plasmodium berghei infection can prevent anemia (tcount = 1.45 â‰¥ ttable = 1.96) but cannot prevent the occurrence of IUGR (tcoun= 1.90 â‰¥ ttable = 1.96) . Conclusion DHP therapy in mice with Plasmodium berghei infection can prevent anemia but can cause the fetus to experience IUGR.Â